Faktor – Faktor yang Mempengaruhi Keberkesanan Amali Kerja Kayu dari Perspektif Pelajar Sekolah Menengah Vokasional di Provinsi Aceh - Lailan Fachrah; Nor Azlina Hasbullah; Ashah Ab Rahman (PTE FTK UIN Ar-Raniry, 2017)
This study aims to identify factors that influence the effectiveness of practical woodworking and determine the effectiveness of woodworking practical from the perspective of students of secondary vocational schools in the province of Aceh. Factors - factors studied were the workshop equipment, workshop environment. This study was designed to investigate the significant differences concerning factors woodworking practical effectiveness based on demographic factors. A total of 130 respondents were randomly selected from six vocational schools in the province of Aceh. The instrument consists of a set of questionnaire consisting of 49 items and distributed second level students. The results showed there is no significant difference between factors - factors woodworking practical effectiveness based on demographic factors except the income level of the parents and the parents’ workplace. This shows there is a significant effect of the four factors, the effectiveness of practical woodworking, accounting for 60.6% (R2 = 0.606) changes in the variance in effectiveness of hands-on woodworking, and between the two of these factors, the workshop environment is the factor that most influences the effectiveness of the practical work wood, contributing 43.3% (R2 = 0.433) of the variance in effectiveness of woodworking practical.